Konsep Islam dan Negara Menurut KH. Achmad Siddiq - Mustofa, Muhammad (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2016)
Abstract: This article discusses the thought of KH. Achmad Siddiq (d. 1991) on the relationship between Islam and the state. He was the spiritual leader of Nahdlatul Ulama from 1984 to1991. He articulated Islam and Indonesia by actualizing the thought of Sunni Islam. He concludes that Islam and the state mutually beneficial. He (1) argues that Pancasila, the state philosophy, contains the principle of monotheism and humanism; (2) constructs pluralistic concept with trilogy of brotherhood, namely islamic brotherhood, national brotherhood, and humanistic brotherhood; (3) creates islam as rahmah li al-‘âlamîn (blessing for the worlds) and maintains the finality of unitary republic of Indonesia.he asserts that Islam and the state is mutually correlated, islam regulates norms and ethic whereas the state is responsible to actualizes those norms and ethic in form of regulatory framework. Thus, religion and the state fortifies each other’s function. Keywords: Islamic political thought, KH. Achmad Siddiq, Nahdlatul Ulama Abtrak: Artikel ini membahas tentang pemikiran KH. Achmad Siddiq tentang Islam dan negara. KH. Achmad Siddiq berusaha mengaktualisasikan Islam dan keindonesiaan dalam format ajaran ahl al-sunnah wa al-jamâ’ah dalam bentuk simbiosis mutualistik berupa: 1) Memaknai Pancasila dengan konsep tauhid yang berbasis humanis, 2) Membangun konsep pluralistik dengan konsep trilogi ukhuwwahnya, yaitu; ukhuwwah Islâmiyyah, ukhuwwah wathaniyyah, dan ukhuwwah basyariyyah, 3) Mewujudkan Islam rahmah li al-‘âlamîn dengan bingkai negara Indonesia berbentuk NKRI yang final dalam usaha merealisasikan mashlahah ‘âmmah. Menurut K.H. Achmad Siddiq, negara dan agama sejatinya ada korelasinya, agama mengatur nilai-nilai kehidupan, di mana agama berperan dalam membentuk nilai-nilai etik, sedangkan negara bertugas mengaktualisasikan nilai-nilai etik dan moral dalam bentuk peraturan perundang-undangan. Agama dan negara saling menguatkan fungsi masing-masing. Kata Kunci: Islam, negara, KH. Achmad Siddiq.